2017
DOI: 10.1042/bsr20170302
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-340 inhibits osteoclast differentiation via repression of MITF

Abstract: Many miRNAs play critical roles in modulating various biological processes of osteoclast differentiation and function. Microphthalmia-associated transcription factor (MITF), a target of miR-340, served as pivotal transcription factor involved in osteoclast differentiation. However, the role of miR-340 and MITF during osteoclast differentiation has not yet been clearly established. Tartrate-resistant acid phosphatase (TRAP) staining assay was performed to identify osteoclasts differentiated from bone marrow-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…Recent studies have shown that miRNAs exert considerable roles in regulating various biological processes of osteoblast and osteoclast differentiation and function, thus making miRNAs as biomarkers and potential targets for osteoporosis therapy . Generally, miRNAs with upregulated expression level during osteoclast differentiation or formation tend to promote osteoclastogenesis, while miRNAs with downregulated level during osteoclast differentiation tend to inhibit osteoclastogenesis . A previous study using micro array analysis revealed the expression profile during different stages of murine osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have shown that miRNAs exert considerable roles in regulating various biological processes of osteoblast and osteoclast differentiation and function, thus making miRNAs as biomarkers and potential targets for osteoporosis therapy . Generally, miRNAs with upregulated expression level during osteoclast differentiation or formation tend to promote osteoclastogenesis, while miRNAs with downregulated level during osteoclast differentiation tend to inhibit osteoclastogenesis . A previous study using micro array analysis revealed the expression profile during different stages of murine osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…23 Generally, miRNAs with upregulated expression level during osteoclast differentiation or formation tend to promote osteoclastogenesis, while miRNAs with downregulated level during osteoclast differentiation tend to inhibit osteoclastogenesis. 24 A previous study using micro array analysis revealed the expression profile during different stages of murine osteoclastogenesis. Among all detected miRNAs, 49 were upregulated and 44 were downregulated, 25 however, miR-20a-5p was not among the list.…”
Section: F I G U R E 6 Knockdown Of Srcin1 Promoted Proliferation Andmentioning
confidence: 99%
“…In addition to transcriptional regulation, as might be expected for a key transcription factor, MITF is also subject to posttranscriptional regulation via both control of its mRNA polyadenylation by CPEB4 (Pérez-Guijarro et al 2016) and the action of microRNAs that play a key role in melanoma biology (Bell and Levy 2011;Kunz 2013). To date, several microRNAs have been described as inhibiting MITF expression, including miR-26a in melanoma (Qian et al 2017), miR-340 in osteoclasts (Zhao et al 2017), and miR-137 (Bemis et al 2008), miR-148 (Haflidadóttir et al 2010, miR-155 (Arts et al 2015), and miR-182 (Yan et al 2012). No doubt future research will identify additional miRs that can affect MITF expression and for now we refer the reader to the microRNA target prediction Web page for the 3 ′ untranslated region (UTR) (TargetScanHuman, http://www.targetscan.org/cgi-bin/ targetscan/vert_72/view_gene.cgi?rs=ENST00000328528 .6&taxid=9606&showcnc=0&shownc=0&shownc_nc=& showncf1=&showncf2=&subset=1).…”
Section: Repressors Of Mitf Mrna Expressionmentioning
confidence: 99%
“…found that miR‐340 inhibited endometrial carcinoma cell viability and proliferation by inducing apoptosis . Additionally, miR‐340 is involved in osteoclast differentiation by repressing microphthalmia‐associated transcription factor . Long noncoding RNA host gene 16 promoted osteosarcoma cell migration and invasion by sponging miRNA‐340 .…”
Section: Discussionmentioning
confidence: 99%
“…45 Additionally, miR-340 is involved in osteoclast differentiation by repressing microphthalmia-associated transcription factor. 46 Long noncoding RNA host gene 16 promoted osteosarcoma cell migration and invasion by sponging miRNA-340. 47 In addition, miR-340 was elevated in the maternal whole blood of patients with gestational diabetes and inversely regulated by insulin and glucose.…”
Section: Discussionmentioning
confidence: 99%